Host and Viral Genetic Variation in HBV-Related Hepatocellular Carcinoma - An, Ping; Xu, Jinghang; Yu, Yanyan; Winkler, Cheryl A. (Frontiers in Genetics, 2018)
Hepatocellular carcinoma (HCC) is the fifth most common cancer in men and the second leading cause of cancer deaths globally. The high prevalence of HCC is due in part to the high prevalence of chronic HBV infection and the high mortality rate is due to the lack of biomarkers for early detection and limited treatment options for late stage HCC. The observed individual variance in development of HCC is attributable to differences in HBV genotype and mutations, host predisposing germline genetic variations, the acquisition of tumor-specific somatic mutations, as well as environmental factors. HBV genotype C and mutations in the preS, basic core promoter (BCP) or HBx regions are associated with an increased risk of HCC. Genome-wide association studies have identified common polymorphisms in KIF1B, HLA-DQ, STAT4 and GRIK1 with altered risk of HBV-related HCC. HBV integration into growth control genes (such as TERT), pro-oncogenic genes, or tumor suppressor genes and the oncogenic activity of truncated HBx promote hepatocarcinogenesis. Somatic mutations in the TERT promoter and classic cancer signaling pathways, including Wnt (CTNNB1), cell cycle regulation (TP53), and epigenetic modification (ARID2 and MLL4) are frequently detected in hepatic tumor tissues. The identification of HBV and host variation associated with tumor initiation and progression has clinical utility for improving early diagnosis and prognosis; whereas the identification of somatic mutations driving tumorigenesis hold promise to inform precision treatment for HCC patients.